Social safety nets in presence of weather shocks: three essays on development economics from village economies in Kenya - Ongudi, Silas Okech (School of Economics, 2022)
This thesis consists of three chapters that contribute towards a better understanding of the important role played by social safety net programs in supporting poor households mitigate the effects of weather shocks, reduce poverty and vulnerability, and increase consumption of healthy food. In achieving this, we undertake an in-depth analysis supported by econometric techniques to analyze the effect of social safety net program (in this case Hunger Safety Net Program, HSNP) on a range of outcomes. In all the chapters, we use data from HSNP transfer collected in the four districts (namely, Turkana, Marsabit, Mandera and Wajir) of Kenya covering 2009-2012. The central theme of this thesis is to contribute towards discussion around the possibility of using social protection policies as adaptation strategy to climate change. In the chapter two, we examine the effects of exposure to drought on child health and ask whether receipt of social safety net, in the form of HSNP cash transfer, could help poor households mitigate the negative effects of drought. Evidence from this study show that children residing in HSNP poor beneficiary households in treated sub-locations and were exposed to drought early in life experienced worse child's weight for age Z- scores by approximately 0.11 standard deviations compared to those in control sub-locations. At the same time, we show that children residing in HSNP poor beneficiary households in treated sublocations and were exposed to cumulative drought observed worse child's height for age Zscores by 0.01 standard deviations compared to those in control sub-locations. Second, we find possibility of remediation for cumulative drought on HAZ scores and on WAZ scores when drought is measured during in utero periods. These results provide suggestive evidence that the effects of drought might be long term in nature and that large investments are needed to cushion households against drought. This chapter contributes to several stands of economic literature. First, it extends the economic discussion on impacts of extreme weather events on child. Secondly, it contributes to the discussion on whether social safety net can help buffer the negative effects of weather-related shocks. Third, it extends the discussion on shocks and consumption smoothing in village economies. Fourth, our paper extendsthe discussion on the differences in gestational processes between male and female children in the developing world. Finally, our paper relates to the literature that links social safety net to climate change mitigation strategies in poor economies. The implications of our results are clear: in that large investments ae necessary in mitigating the effects of extreme weather events. The third chapter investigates whether, for some given households, receipt of social safety net would crowd out or crowd in private transfers received from social network members, and especially when households are exposed to drought. This chapter is motivated by the paucity of empirical evidence on how antipoverty programs affect informal transfers, particularly in poor economies where limited financial resources face competing demands from various sectors. A second motivation relates to the ambiguity of economic theory in predicting the direction and magnitude of transfer derivative (Gibson, Olivia, & Rozelle, 2011). Our result confirm evidence of per shilling crowding out when private transfers are received in non-cash forms. The crowding out effects is stronger at household compared to village levels. This chapter contributes to economic literature in different ways. First, it improves our understanding on the determinants of private transfers received by households by showing that previous level of poverty and drought exposure are important factors. Moreover, it extends the discussion on how households smooth their consumption levels using private transfers. In addition, it contributes to analysis of behavioural implication of receiving public transfer on demographic compositions and characteristics of rural households. Finally, we contribute to crowding out literature by providing evidence from a developing country perspective where such information is hard to find but necessary in helping design policies that account for the socio-economic features of the rural poor in Africa. In the final chapter, we analyze the effect of income (proxied by the receipt of HSNP transfer) on the consumption of nutrients amongst HSNP-beneficiary and non-beneficiary households. This chapter is motivated by the limited empirical evidence on how temporary income impact consumption of nutrients, in instances where risk-sharing practices between communities are strong (Townsend, 1995; Fafchamps and Lund, 2003; Dercon, et al., 2012). Under such setting, the effects of social program can also accrue to non-beneficiary households through familial or community-based channels, and this has a significant effect on the design of policies aimed at reducing extreme poverty and enhancing nutritional uptakes in the rural areas of developing countries. We show that HSNP poor beneficiary households in treated villages consume micronutrients (Heme iron, Vitamin A, C and beta carotene) rich diets, while HSNP non-poor, non- beneficiary households in treated villages consume more Vitamin A rich diets, compared to those in control villages. Further, this paper show that these effects operate through insurance and credit market channels. The implication of these findings are clear: increasing the amount of transfer received by households is likely to reduce malnutrition problem in village economies.